Tai Ji Quan, the brain, and cognition in older adults - Yu-Kai Chang; Yu-Hsiang Nien; Ai-Guo Chen; Jun Yan (Elsevier, 2014)
The relationship between physical activity (PA) and cognition has received much attention recently. While evidence of improved cognition following PA has consistently been observed, the majority of studies have spotlighted aerobic exercise and the effects of other modes of PA, such as Tai Ji Quan, on cognition have received limited attention. This article provides a brief review of the literature concerning the influence of Tai Ji Quan on cognition in older adults, including those with intact cognition and those with cognitive impairment. In addition, this review proposes potential mechanisms (cardiovascular fitness, motor fitness, movement coordination, social interaction, and meditation statuses as well brain structure and function) evaluated from a neuroimaging perspective that may explain the Tai Ji Quan-cognition relationship. Finally, we present suggestions for future research. In conclusion, Tai Ji Quan, with its multi-faceted characteristics, shows promise as a mode of PA for enhancing cognition, as well as brain health, in older adults. Based on the findings in this review, further exploration of the effects of Tai Ji Quan on cognition in older adults is warranted.